The Impact of Religious Commitment on the Components of Entrepreneurship, Productivity, Flexibility, and Emotional Intelligence Among Students of Adib Mazandaran Higher Education Institute - Valipour, Abolfazl; Hashemi Nekoo, Seyed Alireza; Haghighat Monfared, Jalal (International Journal of Education and Cognitive Sciences, 2022)
Purpose: This research explores the correlation between religious commitment and various factors such as age, entrepreneurial motivation, entrepreneurial awareness, entrepreneurial personality, emotional intelligence, human resource productivity, willingness to organizational entrepreneurship, and human resource flexibility. Methods and Materials: To collect information, a questionnaire tool was utilized, while Pearson's correlation tests were conducted using Spss software. A total of 415 responses were collected from the student population at Adib Higher Education Institute of Mazandaran. Findings: Based on the research findings, it is evident that there is a strong correlation between religious commitment and entrepreneurial personality and awareness. Conclusion: Based on the findings of this study, it is evident that there is a strong correlation between religious commitment and emotional intelligence. This suggests that religious commitment can have a significant impact on entrepreneurial intention. In addition to factors such as internal control, innovation, independence, problem-solving ability, and an active personality, which have been found to positively influence entrepreneurial intention